Wombs and Alien Spirits: Women, Men, and the Zār Cult in Northern Sudan - Boddy, Janice (University of Wisconsin Press, 1989)
Based on nearly two years of ethnographic fieldwork in a Muslim village in northern Sudan, Wombs and Alien Spirits explores the zâr cult, the most widely practiced traditional healing cult in Africa. Adherents of the cult are usually women with marital or fertility problems, who are possessed by spirits very different from their own proscribed roles as mothers. Through the woman, the spirit makes demands upon her husband and family and makes provocative comments on village issues, such as the increasing influence of formal Islam or encroaching Western economic domination. In accommodating the spirits, the women are able metaphorically to reformulate everyday discourse to portray consciousness of their own subordination. Janice Boddy examines the moral universe of the village, discussing female circumcision, personhood, kinship, and bodily integrity, then describes the workings of the cult and the effect of possession on the lives of men as well as women. She suggests that spirit possession is a feminist discourse, though a veiled and allegorical one, on women's objectification and subordination. Additionally, the spirit world acts as a foil for village life in the context of rapid historical change and as such provides a focus for cultural resistance that is particularly, though not exclusively, relevant to women.
free
Keywords: Social Science / Anthropology / Cultural & Social; Social Science / General